Conversion of Host Cell Receptor into Virus Destructor by Immunodisc to Neutralize Diverse SARS-CoV-2 Variants - Hwang, Jaehyeon; Kim, Beom Kyu; Moon, Seokoh; Park, Wonbeom; Kim, Kyeong Won; Yoon, Jeong Hyeon; Oh, Hyunseok; Jung, Sangwon; Park, Youngseo; Kim, Suhyun; Kim, Misoo; Kim, Soomin; et al. (Advanced Healthcare Materials, 2024)
The decreasing efficacy of antiviral drugs due to viral mutations highlights the challenge of developing a single agent targeting multiple strains. Using host cell viral receptors as competitive inhibitors is promising, but their low potency and membrane-bound nature have limited this strategy. In this study, the authors show that angiotensin-converting enzyme 2 (ACE2) in a planar membrane patch can effectively neutralize all tested severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants that emerged during the COVID-19 pandemic. The ACE2-incorporated membrane patch implemented using nanodiscs replicated the spike-mediated membrane fusion process outside the host cell, resulting in virus lysis, extracellular RNA release, and potent antiviral activity. While neutralizing antibodies became ineffective as the SARS-CoV-2 evolved to better penetrate host cells the ACE2-incorporated nanodiscs became more potent, highlighting the advantages of using receptor-incorporated nanodiscs for antiviral purposes. ACE2-incorporated immunodisc, an Fc fusion nanodisc developed in this study, completely protected humanized mice infected with SARS-CoV-2 after prolonged retention in the airways. This study demonstrates that the incorporation of viral receptors into immunodisc transforms the entry gate into a potent virucide for all current and future variants, a concept that can be extended to different viruses.
Keywords: Angiotensin-converting enzyme 2; Anti-viral drugs; Cell receptors; Host cells; Immunodisk; Membrane patch; Multiple strains; Nanodisks; Nanoperforator; Single-agent; Angiotensin-Converting Enzyme 2; Animals; Antibodies, Neutralizing; Antibodies, Viral; Antiviral Agents; Chlorocebus aethiops; COVID-19; HEK293 Cells; Humans; Mice; SARS-CoV-2; SARS-CoV-2 variants; Spike Glycoprotein, Coronavirus; Vero Cells; Virus Internalization; ACE2; immunodiscs; nanodiscs; nanoperforators; SARS-CoV; virus